Topical levocabastine—a review of therapeutic efficacy compared with topical sodium cromoglycate and oral terfenadine on days with high pollen counts - Marianela de Azevedo (Mediators of Inflammation)
Levocabastine is a new H1-receptor antagonist specifically developed for the topical treatment of seasonal allergic rhinoconjunctivitis. Clinical experience to date clearly demonstrates that levocabastine eye drops and nasal spray are effective and well tolerated for the treatment of this allergic disorder. Analysis of data from a number of comparative trials reveals that topical levocabastine is at least as effective as sodium cromoglycate and the oral antihistamine terfenadine, even on days with high pollen counts (≥ 50 pollen particles/m3 ) when symptoms are severe. Coupled with a rapid onset of action and twice daily dosing, these findings make topical levocabastine an attractive alternative to other therapeutic approaches as a first-line therapy for the treatment, of this common condition.